Interfacial mechanical behaviour of protein–mineral nanocomposites: A molecular dynamics investigation. (17th May 2018) - Lai, Zheng Bo; Bai, Ruixiang; Lei, Zhenkun; Yan, Cheng
Abstract: Biological composite materials, such as bone, tooth and nacre, are comprised of a mixture of nano-sized hard components (e.g. mineral platelets) and soft components (e.g. protein molecules). Their mechanical behaviour greatly depends on the protein–mineral interfaces. This paper investigates the effects of mineral surface nanostructures on the interfacial interaction and mechanical behaviour of protein–mineral nanocomposites. Interfacial shear between osteopontin (OPN) and hydroxyapatite (HA) mineral layers with surface nanostructures is investigated using the atomistic molecular dynamics (MD) simulations. The results indicate that the OPN residues can be attached to HA surfaces but the surface nanostructures greatly affect the interfacial interaction and mechanical behaviour. The HA layers with a higher number of nano-sized grooves (defects) increase the surface roughness but reduce the pulling force and energy dissipation.